Challenges and complexities of multifrequency atomic force microscopy in liquid environments - Solares, Santiago D. (Beilstein Journal of Nanotechnology, 2014)
This paper illustrates through numerical simulation the complexities encountered in high-damping AFM imaging, as in liquid enviroments, within the specific context of multifrequency atomic force microscopy (AFM). The focus is primarily on (i) the amplitude and phase relaxation of driven higher eigenmodes between successive tip–sample impacts, (ii) the momentary excitation of non-driven higher eigenmodes and (iii) base excitation artifacts. The results and discussion are mostly applicable to the cases where higher eigenmodes are driven in open loop and frequency modulation within bimodal schemes, but some concepts are also applicable to other types of multifrequency operations and to single-eigenmode amplitude and frequency modulation methods.
Keywords: amplitude-modulation; bimodal; frequency-modulation; liquids; multifrequency atomic force microscopy